Back in the Old Country: Homecoming and Belonging in Leonard Kniffel’s A Polish Son in the Motherland: An American’s Journey Home and Kapka Kassabova’s To the Lake: A Balkan Journey of War and Peace - Rutkowska, Małgorzata (Text Matters: A Journal of Literature, Theory and Culture, 2024)
Homecoming travel narratives are typically written by first-wave immigrants, their children, or grandchildren. Usually, homecoming books are accounts of emotionally charged travels that oscillate between nostalgia and idealization of the ancestral land on the one hand and a sense of grief, loss and unbelonging on the other. The present paper examines two homecoming travel narratives that sidestep such pitfalls: Leonard Kniffel’s A Polish Son in the Motherland: An American’s Journey Home (2005) and Kapka Kassabova’s To the Lake: A Balkan Journey of War and Peace (2020). For both authors, a starting point of the journey is a deep bond with their late maternal grandmothers, whose stories of “the old country” have shaped their sense of identity. Neither Kniffel, a Polish-American author, nor Kassabova, a Bulgarian-born writer writing in English, has ever lived in the countries their grandmothers left as young women—Poland and Macedonia. Return travels not only allow them to better understand the interplay of past and present in their immigrant family history but also to accept their homeland as a complex historical, cultural, and personal legacy. Thus, in both books, returning to the ancestral homeland, undertaken at mid-life, is represented as an essential stage in one’s life journey, which results in a symbolic sense of closure and restoration.